Macrófitas aquáticas como ingrediente para suplementação de ração de peixe e de alimento vivo (cladóceros) na piscicultura sustentável de pequena escala - Proença, Maíra Alcântara (2019)
The increasing demand and especially the consumption of fish has been growing exponentially as a consequence of increasing human population and also due to the search for healthier foods. Sustainable food production systems are essential to meet such demands. It is believed that small scale fish-farming can play relevant role in this great chalenge yet to be solved in this century. New technologies contributing to improve the production of live food and to better food rations for fish nutrition at low cost and with environmentally friendly practices must be adressed by future researches. The present study aimed to test the adequacy of the biomass of the macrophytes Hydrilla verticillata and Pistia stratiotes as an ingredient to supplement to fish rations and to supplement algas suspensions to be used as food in cladocerans cultures.Three fish rations were produced with the inclusión of macrophyte biomass at 5%, 10% and 15% supplementation levels, and tested for the Nile tilapia, Oreochromis niloticus. Three inclusion levels of macrophyte biomass were also used to supplement the algal suspension used to feed the cladocerans Ceriodaphnia silvestii and Daphnia similis in laboratory cultures. Chemical, biochemical and caloric energy content analyses were performed to characterize macrophyte biomass, comercial ration and the three supplemented experimental fish rations. Kinectics and release of nutrients from macrophyte biomass, and supplemented rations were quantified and modelled. The results showed that H. verticillata had higher fiber content but lower amounts of protein, as compared with P. stratiotes. Ration supplemented with 10% of H.verticillata biomass had lower nutrient liberation than control and the best growt performance with weight gain of 297.61% the initial fish weight. Rations with inclusion of P. stratiotes biomass were not significantly diferent from control in relation to O. niloticus growth, which had a total of 307,6% body weight 60 days after the beginning of the experiment. Among cladocerans C. silvestrii had a better performance when fed on algal suspension supplemented with 66% of H. verticillata macrophyte biomass. On the other hand, D. similis reached best growth performance when fed only with algal suspension, as food source. Therefore, taking in consideration the maximum levels of successful inclusion of macrophyte biomass indicates potential to be used as ingredient to fish rations. It was also promising the environmental advantage conferred by the lower liberation of nitrogen to the water by H. verticillata biomass. It can be concluded that the use of macrophyte biomass is viable at the levels of 10% and 15% for H. verticillata and P. stratiotes, respectively, with nutritional, economical and environmental advantages and can contribute to the expansion of small scale pisciculture as a strategy to reduce costs aiming sustainable pisciculture.